Discursos na imprensa sobre índios e caboclos durante o Contestado: o caso do Diário da Tarde - Wiik, Flávio Braune; Simonetti, Rafael Pereira [UNESP] (Universidade Estadual de Maringa, 2017)
Taking into account aspects presented in articles about Brazilian Native Indians and Caboclos from the Contestado region during its main battles (1912-1916) published in the newspaper O Diário da Tarde, this essay identifies new insights on the perceptions about its local population. It includes descriptions about conflicts involving Indians and Caboclos, their specific characteristics and contrasts between the two segments. The social thought of that period has been used as the background of the proposed analysis.
Speeches in the press about indigenous and caboclos during Contestado: The case of Diário da Tarde
Keywords: Brazilian Indians; Caboclos; Contestado; O Diário da Tarde